Analysis of the Anti-Inflammatory Potential of Pure and Microemulsified Bullfrog Oil in Acute Lung Injury - Davim, André Luiz Silva; Dantas, Tereza Neuma de Castro; Pereira, Márcia Rodrigues (Journal of Morphological Sciences, 2018)
Infectious diseases account for more than a third of all hospital admissions, and are highly prevalent in intensive care units. Currently, sepsis is one of the diseases with the highest morbidity and mortality rates worldwide, with death rates reaching up to 60% among intensive care patients, according to statistics from low-income countries. The prominence of multi-resistant microorganisms is rising, while the possibilities of development of new target drugs are being exhausted. Thus, the objective of the present study was to evaluate the anti-inflammatory potential of bullfrog oil in its pure state and in a microemulsion system in an experimental model of sepsis. Mice were separated into three groups and treated with bullfrog oil in its pure state, in a microemulsion, and with saline solution, and subsequently submitted to induction of sepsis. Bronchoalveolar lavages were performed for cell counts, as well as analyses of lung tissue samples. When the washings were analyzed, no statistically significant difference was observed in cell migration between the experimental groups, but a difference was observed between these groups and the saline solution group. When the lung tissue samples were analyzed, intense tissue wear was observed in the bullfrog oil groups, with the presence of cellular infiltrate and rupture of respiratory bronchioles and alveoli. However, in the microemulsion group, no major tissue wear was observed, and the pulmonary parenchyma was more preserved. Thus, we concluded that bullfrog oil in pure form and in a microemulsion system are good modulators of the inflammatory response, with the microemulsion system being more efficient in protecting lung tissue.
Keywords: sepsis; bullfrog oil; microemulsion system; acute lung injury